Tracking time-varying structural responses of in-service cable-stayed bridges with model parameter errors and concrete time-dependent effects. (March 2022) - Sun, Huahuai; Chen, Weizhen; Cai, Shunyao; Zhang, Boshan
Abstract: To track time-varying structural responses of in-service cable-stayed bridges, a numerical method considering model parameter errors and concrete time-dependent effects is presented. The finite element model updating of a cable-stayed bridge could be formed as a multi-objective optimization problem, where the updating parameters were selected by sensitivity analysis, the objective functions were constructed based on the first cable forces measurement, and the formed multi-objective optimization problem was solved by the genetic algorithm. On the basis of the updated model, the step-by-step finite element method was employed to track the structural responses of a cable-stayed bridge with concrete time-dependent effects. Also, the numerical method was verified by the actual structural responses collected by periodic on-site inspections on a cable-stayed bridge example. The results indicate that the presented method can effectively track the time-varying structural responses of existing cable-stayed bridges. The relative cable force difference between the numerical results and the periodic measurements remains within ± 10%, while the relative difference of the maximum girder deflection is 4.04% after 12 years in service. From 10 to 12 years in service, the maximum girder deflection of a cable-stayed bridge example increased from 0.264 m to 0.285 m.